2017
DOI: 10.1186/s40101-016-0125-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the oxytocin receptor gene (OXTR) rs53576 polymorphism and emotional processing of social and nonsocial cues: an event-related potential (ERP) study

Abstract: BackgroundOxytocin receptor (OXTR) gene polymorphisms are related to individual differences in emotional processing of social cues. However, whether OXTR polymorphisms affect emotional processing of nonsocial cues remains unclear. The present study investigated the relationship between the OXTR rs53576 polymorphism and emotional processing of social cues and nonsocial cues.MethodsEvent-related potentials were recorded from 88 male participants while images of humans and images of objects were presented as soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
(92 reference statements)
2
5
0
1
Order By: Relevance
“…Genotyping of OXTR rs53576 revealed that 77 children had the GG genotype (13.6%), 257 children the GA genotype (45.3%), and 234 children had the AA genotype (41.2%) (Hardy-Weinberg equilibrium: χ 2 = 0.232, p = 0.630). This genotypic frequency in the participants was consistent with those of previous studies which have reported that the frequency of the AA genotype of OXTR rs53576 is relatively high for populations in East Asia 7,22,34 . Given that patients with the GG and GA genotypes share common psychological characteristics 13,19 as mentioned above, we amalgamated subjects with GG and GA genotypes into one group, as has been done in previous studies 13,19,22,34 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Genotyping of OXTR rs53576 revealed that 77 children had the GG genotype (13.6%), 257 children the GA genotype (45.3%), and 234 children had the AA genotype (41.2%) (Hardy-Weinberg equilibrium: χ 2 = 0.232, p = 0.630). This genotypic frequency in the participants was consistent with those of previous studies which have reported that the frequency of the AA genotype of OXTR rs53576 is relatively high for populations in East Asia 7,22,34 . Given that patients with the GG and GA genotypes share common psychological characteristics 13,19 as mentioned above, we amalgamated subjects with GG and GA genotypes into one group, as has been done in previous studies 13,19,22,34 .…”
Section: Resultssupporting
confidence: 92%
“…The human OXTR gene is located on chromosome 3p25, spans 17 kb and contains four exons and three introns 6 . A single nucleotide polymorphism (SNP) within intron 3 of the OXTR gene, rs53576, is a widely investigated SNP due to its association with individual differences in social behaviours 79 . Furthermore, it has been reported that OXTR rs53576 is related to variability of phenotypes in mental health (reviewed in 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent ERP study found that male G/G relative to A/A carriers of OXTR rs53576 showed larger N1 amplitudes in response to images of both humans and objects and larger N2 amplitudes in response to images of humans but not objects (Choi et al , 2017). These findings have been proposed to indicate that OXTR rs53576 may affect emotional processing of both social and nonsocial cues.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also showed that people with the GG genotype exhibit higher emotional stability which was associated with greater perceived social support and in turn general self-reported health (10). Notably, empathy and greater awareness of social cues have been consistently related to having a GG genotype [1214].…”
Section: Introductionmentioning
confidence: 99%